Selective Synthesis and Molecular Structure of Novel Aminooxyglycosyl Derivatives Bearing Hydroxyphenyl Moieties. Issue 2 (16th January 2020) - Lafuente, Leticia; Santiago, Cintia C.; Rojas, Agustín H.; Piro, Oscar E.; Echeverría, Gustavo A.; Ponzinibbio, Agustín
Abstract: We present the selective synthesis of novel aminooxy glycosyl derivatives bearing hydroxy phenyl moieties. A strict control over the anomeric and E / Z configurations has been achieved. The products obtained are α‐glycosides and the aromatic moiety substitute the Schiff's base trans to the O‐glycosidic bond. Single crystal X‐ray diffraction and NMR spectral data are reported and analysed. Abstract : A simple route for the synthesis of novel aminooxy glycosides from D‐glycals has been described. The products were obtained in good overall yields, with high anomeric and E/Z stereo control. The new compounds obtained are α‐glycosides and the aromatic moiety substitute the Schiff's base in a trans fashion respect to the O ‐glycosidic bond. Structural characteristics, including conformations, were determined in solution by NMR spectrometry and in solid state by X‐ray diffraction techniques.